To dope or not to dope: Elite athletes' perceptions of doping deterrents and incentives - Overbye, M.; Lykke Knudsen, M.; Pfister, G. (Performance Enhancement & Health, 2013)
This study aims to examine the circumstances which athletes say affect their (hypothetical) considerations of whether to dope or not and explore the differences between athletes of different gender, age and sport type.